2020
DOI: 10.3389/feart.2020.00310
|View full text |Cite
|
Sign up to set email alerts
|

Defining Pre-eruptive Conditions of the Havre 2012 Submarine Rhyolite Eruption Using Crystal Archives

Abstract: The 2012 Havre eruption evacuated a crystal-poor rhyolite (∼3-7% crystals) producing a volumetrically dominant (∼1.4 km 3 ) pumice raft, as well as seafloor giant pumice (5-8%) and lavas (12-14%) at the vent (∼0.1 km 3 ), both of which have subtly higher phenocryst contents. For crystal-poor rhyolites like the Havre pumice, it can often remain ambiguous as to whether the few phenocrysts present, in this case, plagioclase, orthopyroxene, clinopyroxene, Fe-Ti oxides ± quartz, are: (a) autocrysts crystallizing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Given these limitations in determining what might be appropriate crustal materials and compositions to partially melt, we test the viability of a model that invokes extensive fractional crystallization. We have previously shown that the 2012 Havre medium-K rhyolite can be generated by limited fractional crystallization (7%) from a starting composition represented by a dredged Havre flank dacite (~67 wt% SiO 2 ; Knafelc et al, 2020). Herein, we explore the idea that this dacite composition is ultimately derived from a basaltic parent.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Given these limitations in determining what might be appropriate crustal materials and compositions to partially melt, we test the viability of a model that invokes extensive fractional crystallization. We have previously shown that the 2012 Havre medium-K rhyolite can be generated by limited fractional crystallization (7%) from a starting composition represented by a dredged Havre flank dacite (~67 wt% SiO 2 ; Knafelc et al, 2020). Herein, we explore the idea that this dacite composition is ultimately derived from a basaltic parent.…”
Section: Introductionmentioning
confidence: 93%
“…An effusive exit velocity of approximately 14 ms −1 was estimated to produce the pumice raft based on magma ascent models inputting seafloor pumice properties (Manga et al, 2018). However, more recent work has shown that when only utilizing seafloor pumice properties, eruption rates of the associated pumice rafts could be considerably underestimated (Knafelc et al, 2020;Mitchell et al, 2021;Knafelc et al, 2022). Most recently, the Havre 2012 eruption model has been expanded to include a shortlived, violent explosive eruption, capable of ejecting hot pyroclasts through the 900 m water column into the atmosphere, which then air-cooled to be deposited at the ocean surface, producing the pumice raft (Knafelc et al, 2022).…”
Section: The Havre 2012 Eruptionmentioning
confidence: 99%
See 3 more Smart Citations